Political and development correlates of social media participation in government: A global survey of national leadership websites - Katz, James; Halpren, Daniel (2013)
This study examines the extent to which national governments are using Web-2.0 applications to increase transparency and engage citizens in decision-making processes. Based on a typology of governmental websites that distinguishes among executive office sites, government web portals and personal websites of heads of government, 160 websites from 82 different countries were examined, and results show that 70 percent of the websites do not offer any participatory services and surprisingly no positive relationships were found between e-participation and variables traditionally associated with e-government implementation. However, a difference between broadband and Internet penetration levels was found: whereas Internet was positively related to e-participation, broadband was only related to the release of information by governments, which is consistent with citizen pressure models of policy change. - Reproduced.
Keywords: E governance